α4(+)β7(hi)CD4(+) Memory T cells Harbor Most Th-17 cells and are Preferentially Infected During Acute SIV Infection - Kader, Muhamuda (2009)
HIV/SIV are thought to infect minimally activated CD4(+) T cells after viral entry. Not much is known about why SIV selectively targets these cells. Here we show that CD4(+) T cells that express high levels of the α4β7 heterodimer are preferentially infected very early during the course of SIV infection. At day 2–4 post infection, α4(+)β7(hi)CD4(+) T cells had ∼ 5x more SIV-gag DNA than β7(−)CD4(+) T cells. α4(+)β7(hi)CD4(+) T cells displayed a predominantly central memory (CD45RA(−)CD28(+)CCR7(+)) and resting (CD25(−)CD69(−)HLA-DR(−)Ki-67(−)) phenotype. Though the expression of detectable CCR5 was variable on α4(+)β7(hi) and β7(−)CD4(+) T cells, both CCR5(+) and CCR5(−) subsets of α4(+)β7(hi) and β7(−)CD4(+) T cells were found to express sufficient levels of CCR5 mRNA suggesting that both these subsets could be efficiently infected by SIV. In line with this, we found similar levels of SIV infection in β7(−)CD4(+)CCR5(+) and β7(−)CD4(+)CCR5− T cells. α4β7(hi)CD4(+) T cells were found to harbor most Th-17 cells that were significantly depleted during acute SIV infection. Taken together, our results show that resting memory α4(+)β7(hi)CD4(+) T cells in blood are preferentially depleted during acute SIV infection, and the loss of these cells alters the balance between Th-17 and Th-1 responses thereby contributing to disease pathogenesis.